DIGITAL INCLUSION OF WOMEN IN ONLINE BUYING AND SELLING PRACTICES - Rika Oktavia; Elsy Renie (Al Ushuliy: Jurnal Mahasiswa Syariah dan Hukum, 2024)
This research examines the digital inclusion of women in online buying and selling practices, analyzing their role as consumers and the impact on economic inclusion. The study employs qualitative research methods (Library Research). The findings indicate that women's participation as consumers in online commerce plays a crucial role in maintaining economic balance and sustainability, particularly by enhancing time efficiency, enabling women to manage household responsibilities effectively. According to the perspective of muamalah fiqh, women's engagement in online buying and selling is permissible under specific conditions. However, it prohibits excessive and wasteful consumption patterns, categorized as al-israf behavior.